Characterization of q-Ces`aro convergence for double sequences - TAȘ, Emre; ORHAN, Cihan (Studia Universitatis Babeș-Bolyai Mathematica, 2017)
In the present paper we examine the Buck-Pollard property of 4- dimensional q-Cesàro matrices. Indeed we discuss some questions related to the q-Cesàro summability of subsequences of a given double sequence. The main re- sult states that “ a bounded double sequence is q-Cesàro summable to L if and only if almost all of its subsequences are q-Cesàro summable to 21−q L”. Mathematics Subject Classification (2010): 40B05, 40C05, 28A12.